Tomorrow’s Dreams: Left-Behind Children and Migration Effects on Their Future Aspirations - Chu, Shareena; Miranda1, Jerica; Tapang, Abbygaile; Balagtas, Paul Anthony S.; Credo, Chillet G.; Pineda, Maica S. (Future Science / FSH-PH Publications, 2025)
This study investigated how parental migration affected the future aspirations of left-behind children of Overseas Filipino Workers (OFWs) in Angeles City, Philippines. With a qualitative explanatory case study approach, the research focused on understanding the impact of parental migration on future aspirations among students at Angeles University Foundation. Through semi-structured interviews with a purposively sampled group of three participants, the study explored the complex interplay of factors influencing their aspirations. Findings suggest that while parental migration introduces challenges like emotional distance and altered family dynamics, it also fosters resilience, financial opportunities, and a strong motivation, often linked to reciprocating parental sacrifices. Key themes emerging included navigating expectations and responsibilities, forging futures amidst parental absence, the duality of migration's impact (both positive and negative), and the crucial role of resilience and support systems. Support from various sources, including teachers and peers, appeared significant. While the small sample size limits the generalizability of the findings, this study emphasizes the importance for educators to provide targeted support addressing the unique educational and emotional needs of left-behind children. It contributes nuanced insights into the impact of migration on family dynamics and children's aspirations, emphasizing the need for strategies to support these children